N-Methyl-D-Aspartate (NMDA) Receptors: Therapeutic Target against Cancer - Raj Kumar Koiri; Aditi Mehrotra (International Journal of Immunotherapy and Cancer Research - Peertechz Publications, 2015)
Glutamate mainly acts as an excitatory neurotransmitter in the central nervous system controlling variety of neuro-physiological functions like synaptic signaling, learning, memory, etc. However, uncontrolled or excessive production of glutamate is neurotoxic and can damage neurons by over activation of glutamate receptors termed as "glutamate excitotoxicity". Apart from excitatory neurotransmitter role of glutamate, some recent observations suggest glutamate as a potential growth factor for tumor development. Till date suitable therapy for cancer is lagging behind due to several side effects. In the present review article, a link between ionotropic glutamate receptor i.e. N-methyl- D-aspartate (NMDA) receptors (NMDARs) and cancer has been mainly focused. Regulation of cancer cells by NMDARs is an emerging or evolving concept. Besides neurons, NMDAR subunits are expressed in various types of cancer cells. Based upon existing literature, we suggest that NMDARs could serve as a therapeutic target against various types of cancer.